Layered materials for energy applications : electrochemistry and toxicity studies - Naziah Mohamad Latiff (2019)
With climate change, global warming, depleting amount of fossil fuels and rising energy demands, it becomes critical for us to search for practical energy solutions. In this endeavor, layered materials such as graphene, transition metal dichalcogenides (TMDs), semiconductor chalcogenides, metal phosphorus chalcogenides and black phosphorus have demonstrated promising properties as new materials for applications in enhanced energy storage and generation systems such as batteries, supercapacitors and fuel cells. In the heart of these devices, electrochemistry plays a central role in their operation. Therefore, we are interested to investigate the electrochemical properties of layered materials to develop on their performance for such applications. To further advance our current understanding in these areas, we studied the effect of dopants in microwave exfoliated graphene on their capacitive performance, as well as the effect of valence and oxide impurities in two common TMDs (i.e. MoS2 and WS2) on their electrocatalytic hydrogen production for use in fuel cells. Besides technological advancement, we also recognize that there is growing concern over the potential health and environmental hazards posed by these layered materials. As such, we have investigated the cytotoxicity of several new emerging layered materials to conduct preliminary toxicological studies. We have chosen vanadium dichalcogenides, semiconductor chalcogenides (i.e. GaSe, GeS), metal phosphorus chalcogenides and black phosphorus to address this research gap. This was performed by incubating the test materials with human lung cancer epithelial cells (A549) for 24 hours and subsequently measuring the remaining cell viabilities using two well-established assays; water-soluble tetrazolium salt (WST-8) and methyl-thiazolyldiphenyl-tetrazolium bromide (MTT). The A549 cell line was chosen since the lung is most likely to be the first organ of contact when they enter the body through inhalation. These electrochemical and cytotoxicity studies would be useful for the progression of our endeavour towards sustainable clean energy.